Effects of Piper betle fractionated extracts on inhibition of Streptococcus mutans and Streptococcus intermedius - Pimpak Phumat (2018)
The overgrowth of certain strains of normal flora in oral cavity can cause many kinds of oral infections or diseases such as carries, periodontitis, and gingivitis. Prevention and treatment of these diseases are usually achieved by chemical antiseptics. However, these chemicals are found as negative impacts of human health hazards and accession of microbial resistance. The present study explores the potential of Piper betle extracts on inhibition of two oral pathogenic bacteria; Streptococcus mutans DMST 41283 and Streptococcus intermedius DMST 42700. P. betle demonstrated significantly higher inhibitory activity against both pathogenic strains than Acacia catechu, Camellia sinensis, Coccinia grandis, Solanum indicum, and Streblus asper. Among fractionated extracts of P. betle from several solvents, the extract from ethyl acetate (Pb-EtOAc) possessed the widest inhibition zone of 11.0 ± 0.1 and 11.3 ± 0.4 mm against both bacterial strains, respectively. Pb-EtOAc showed the same minimum inhibitory concentration of 0.5 mg/mL against both strains, whereas its minimum bactericidal concentrations were 2.0 and 0.5 mg/mL against S. mutans and S. intermedius, respectively. HPLC analysis demonstrated that the major active compound of Pb-EtOAc was 4-allylpyrocatechol. It was found that the killing kinetics of Pb-EtOAc against both test strains were time and dose dependent. Scanning electron microscopy micrographs showed the morphological changes and depletion of the tested pathogens indicating cell destruction after exposure to Pb-EtOAc. It is confirmed that Pb-EtOAc is potentially effective against both oral pathogens and might be used as natural alternative agents in prevention and treatment of oral infections caused by oral pathogenic bacteria.